2020
DOI: 10.1186/s12889-020-8301-0
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of hand-hygiene and environmental-disinfection interventions in settings with children

Abstract: Background: Helping adults and children develop better hygiene habits is an important public health focus. As infection causing bacteria can live on one's body and in the surrounding environment, more effective interventions should simultaneously encourage personal-hygiene (e.g. hand-hygiene) and environmental-disinfecting (e.g. cleaning surfaces). To inform the development of a future multi-faceted intervention to improve public health, a systematic literature review was conducted on behavior change intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 57 publications
2
42
1
4
Order By: Relevance
“…Factors found to be influencing availability of basic handwashing facilities and consistent behaviour towards handwashing practice in the health care settings [ 14 ] and schools [ 8 ] have been explored in several studies. Existing community-based research to date has tended to focus on evaluation of sanitation and hygiene-related interventions rather than nationwide coverage and the associated factors [ 15 , 16 ]. As a result, despite the importance of community-level handwashing facility, there remains a paucity of evidence on the coverage and the influencing factors.…”
Section: Introductionmentioning
confidence: 99%
“…Factors found to be influencing availability of basic handwashing facilities and consistent behaviour towards handwashing practice in the health care settings [ 14 ] and schools [ 8 ] have been explored in several studies. Existing community-based research to date has tended to focus on evaluation of sanitation and hygiene-related interventions rather than nationwide coverage and the associated factors [ 15 , 16 ]. As a result, despite the importance of community-level handwashing facility, there remains a paucity of evidence on the coverage and the influencing factors.…”
Section: Introductionmentioning
confidence: 99%
“…The hand-washing habits of nurses are debatable for many reasons, which include the cumbersome structure of intensive care units, the characteristics of the patients in intensive care, the heavy workload in such units, and an insufficiency of nurses. [ 3 4 ] Undeniably, with varied environmental factors and host factors, human skin is known to be immutably covered with microorganisms, both commensals and pathogens depending on topography. Either hospital surroundings or poor hygiene is one of the key factors of transient micro-flora on the hand which is dynamically responsible for cross-infections.…”
Section: Introductionmentioning
confidence: 99%
“…In our review, this covered a very wide range of issues: socio-economic issues such as having low income, societal issues like the in uence of media, health system issues like vaccine supply and cost, and individual access issues like distance and time. This was found to be a catch all category in many previous reviews of clinicians and patients using the TDF 12,[15][16][17][18][19] , so is not limited to the issue of vaccination barriers. For example, a review of barriers to low back pain guidelines found this domain was common to 4/5 clinician behaviours while many other domains were not covered at all 17 .…”
Section: Discussionmentioning
confidence: 99%